An approach to estimate the saving from negotiation based on cost- benefit anaylsis model - Sabrina, Ahmad; Noor Azilah, Draman @ Muda; Azah Kamilah, Draman @ Muda; Zahriah, Othman (2011)
This paper presents an approach to estimate the savings from implementing negotiation in requirements elicitation process. The aim of implementing negotiation is to minimize the possibility of introducing defects during the creation of requirements and to decrease later effort required to fix requirements defects. An empirical evaluation study is adopted through a role play experiment to evaluate the benefit of exercising negotiation. The net-gain and the return-oninvestment show positive value which suggest that negotiation activities worth an investment. Based on the return-oninvestment of 197 percent in average, this paper suggests that negotiation is a useful prevention activity to inhibit defects from occurring during the creation of requirements.